A mixed methods systematic review of midwives' clinical practices related to prenatal care of women with obesity. (June 2023) - Hyer, Suzanne; Davis, Jean W.; Slowik, Jordan Lee; Dove-Medows, Emily; Giurgescu, Carmen
Highlights: There is a lack of knowledge, confidence, and support for managing maternal obesity Midwives desire a sensitive approach to discussing obesity and maternal obesity Barriers to practices were due to lack of education, guidance, or resources Individual and system-level changes may help overcome these challenges Abstract: Objective: Maternal obesity has been related to adverse maternal and infant outcomes. It is a persistent challenge of midwifery care worldwide and can present clinical challenges and complications. This review sought to identify evidence on the practice patterns of midwives related to prenatal care of women with obesity. Methods: The databases Academic Search Premier, APA PsycInfo, CINAHL PLUS with Full Text, Health Source: Nursing/Academic Edition, and MEDLINE were searched November 2021. Search terms included weight, obesity, practices, and midwives. Inclusion criteria included quantitative, qualitative, and mixed method studies that addressed practice patterns of midwives related to prenatal care of women with obesity published in peer-reviewed journals, written in English. The recommended Joanna Briggs Institute approach to mixed methods systematic reviews was followed e.g. study selection, critical appraisal, data extraction, and a convergent segregated method of data synthesis and integration. Results: Seventeen articles from 16 studies were included. The quantitative evidence showed a lack of knowledge, confidence, and support for midwives that would facilitate adequate management of pregnant women with obesity while the qualitative evidence revealed that midwives desire a sensitive approach to discussing obesity and the risks associated with maternal obesity. Discussion: Quantitative and qualitative literature report consistent individual and system-level barriers to implementing evidence-based practices. Implicit bias training, midwifery curriculum updates, and the use of patient centered care models may help overcome these challenges.